Changes in hypertension prevalence, awareness, treatment and control rates over 20 years in National Capital Region of India: results from a repeat cross-sectional study. Issue 7 (12th July 2017) - Roy, Ambuj; Praveen, Pradeep A; Amarchand, Ritvik; Ramakrishnan, Lakshmy; Gupta, Ruby; Kondal, Dimple; Singh, Kalpana; Sharma, Meenakshi; Shukla, Deepak Kumar; Tandon, Nikhil; Reddy, Kolli Srinath; Krishnan, Anand; et al.
Abstract : Background and objectives: Despite being one of the leading risk factors of cardiovascular mortality, there are limited data on changes in hypertension burden and management from India. This study evaluates trend in the prevalence, awareness, treatment and control of hypertension in the urban and rural areas of India's National Capital Region (NCR). Design and setting: Two representative cross-sectional surveys were conducted in urban and rural areas (survey 1 (1991–1994); survey 2 (2010–2012)) of NCR using similar methodologies. Participants: A total of 3048 (mean age: 46.8±9.0 years; 52.3% women) and 2052 (mean age: 46.5±8.4 years; 54.2% women) subjects of urban areas and 2487 (mean age: 46.6±8.8 years; 57.0% women) and 1917 (mean age: 46.5±8.5 years; 51.3% women) subjects of rural areas were included in survey 1 and survey 2, respectively. Primary and secondary outcome measures: Hypertension was defined as per Joint National Committee VII guidelines. Structured questionnaire was used to measure the awareness and treatment status of hypertension. A mean systolic blood pressure <140 mm Hg and diastolic blood pressure <90 mm Hg was defined as control of hypertension among the participants with hypertension. Results: The age and sex standardised prevalence of hypertension increased from 23.0% to 42.2% (p<0.001) and 11.2% to 28.9% (p<0.001) in urban and rural NCR, respectively. In both surveys, those with high education, alcohol use, obesity and high fasting blood glucose were at a higher risk for hypertension. However, the change in hypertension prevalence between the surveys was independent of these risk factors (adjusted OR (95% CI): urban (2.3 (2.0 to 2.7)) rural (3.1 (2.4 to 4.0))). Overall, there was no improvement in awareness, treatment and control rates of hypertension in the population. Conclusion: There was marked increase in prevalence of hypertension over two decades with no improvement in management.